The Problem of Evil: A Study of Alvin Plantinga’s Free Will Defense - Nur Hadi Ihsan; Muhammad Kholid Muslih; Zalfaa' 'Afaaf Zhoofiroh; Alfiyya Zahra Asso; Najib Abdussalam (Center of Islamic and Occidental Studies, 2026)
This article examines the problem of evil by critically analyzing Alvin Plantinga's Free Will Defense (FWD) and its dialogue with Islamic theology. Employing conceptual analysis and comparative theology, the study investigates Plantinga's notions of libertarian freedom, transworld depravity, and the distinction between moral and natural evil. It compares them with the Ashʿarite doctrine of kasb, Māturīdī conceptions of human agency, al-Ghazālī's understanding of divine wisdom, and Ibn Taymiyyah's teleological perspective. The study finds that Plantinga's Free Will Defense successfully neutralizes the logical problem of evil by demonstrating the logical compatibility between God and evil. However, it does not adequately address the evidential problem of evil and struggles to explain natural evil. Islamic theological perspectives broaden the discussion by emphasizing divine wisdom, moral responsibility, and metaphysical purpose. The study concludes that the problem of evil is not merely a question of logical consistency but also one of meaning and intelligibility, thereby opening a constructive dialogue between analytic philosophy of religion and Islamic kalām.